One pot conversion of furfural to 2-methylfuran in the presence of PtCo bimetallic catalyst - Dohade, M.G.; Dhepe, P. L. (Clean Technologies and Environmental Policy, 2018)
Biomass-derived furfural (FAL) is the platform chemical for synthesis of various value-added chemicals and fuels. One of the FAL-derived chemicals, i.e., 2-methylfuran (2-MF), is the potential biofuel due to its attractive chemical and physical properties. Various methods are reported for conversion of FAL to 2-MF which are operated at high temperature and high H2 pressure. In present work, one pot catalytic method was developed in batch mode process for conversion of FAL to 2-MF. Reactions are carried out in the presence of PtCo/C bimetallic catalyst under 0.5–1 MPa H2 pressure. Monometallic and bimetallic catalysts with different Pt and Co loading were prepared by wet impregnation method, and catalysts were characterized by transmission electron microscopy, BET surface area, X-ray photoelectron spectroscopy, X-ray diffraction and inductive coupled plasma atomic emission spectroscopy techniques. 59% 2-MF yield was achieved at 180 °C and lower (0.5 MPa) H2 pressure.
Keywords: 2-Methylfuran; Bimetallic catalyst; Co-impregnation; furfural; Hydrodeoxygenation; Hydrogenation

Hierarchical K/LTL zeolite as solid base for aqueous phase hydrogenation of xylose to xylitol - Tangale N. P.; Niphadkar, P. S.; Joshi, P. N.; Dhepe, P. L. (Microporous and Mesoporous Materials, 2019)
Post-synthesis modification by alkali treatment was employed for the synthesis of hierarchical K/LTL zeolites with varying degree of mesoporosity. For the alkali treatment, the concentration of aqueous KOH solution was changed from 0.3 to 2.8 M keeping the quantity per gram of zeolite fixed. The influence of the alkali concentration on the chemical composition, powder XRD crystallinity, morphology, basicity, and the textural properties of resultant hierarchical zeolites was investigated. Variation in the concentration of KOH solution was found to control the degree of preferential desilication with the preserved structural fingerprint of K/LTL zeolite. As a result, the generation of mesoporosity was observed along with 1) the decrease in the Si/Al ratio and percentage relative crystallinity, and 2) an increase in BET surface area and mesopore volume. 27Al MAS-NMR results showed that all the aluminum atoms present in the tetrahedral coordination after alkali treatment, which provides an elegant approach for significantly increasing the basic sites in the hierarchical zeolites. As a heterogeneous catalyst, the hierarchical K/LTL zeolites demonstrated the improved performance in the hydrogenation of xylose to xylitol as compared to the parent K/LTL zeolite. The different process parameters were assessed in order to maximize the hydrogenation activity. Among all the hierarchical zeolites, the enhanced catalytic activity was shown by the hierarchical K/LTL prepared by using 1.5 M KOH solution when it is used along with the 3.5 wt% platinum loaded γ-Al2O3 catalyst. This optimum activity may be attributed to the higher surface area, accessible basic sites, nano-sized Pt on γ-Al2O3, and the development of substantial intracrystalline mesoporosity for the enhanced molecular diffusion of reactant to and from the hierarchical zeolite with better-preserved crystallinity.

Photocatalytic hydrogen evolution by MoO3@g-C3N4 and MoO3@f-MWCNT nanocomposites in deionized and natural seawater under visible light - Kangutkar, Raju S.; Walko, Priyanka; Dhepe, P. L.; Nayaka, G. P.; Manjanna, J. (ACS Applied Nano Materials, 2025)
Visible-light-driven photocatalysts are predominantly useful for converting solar to hydrogen energy via photocatalytic water-splitting reactions. The heterojunction composite materials have exhibited remarkable advantages for visible-light photocatalytic H-2 evolution. We have successfully synthesized MoO3@f-MWCNT and MoO3@g-C3N4 nanocomposites and characterized them using PXRD, UV-DRS, Raman spectroscopy, XPS, PL, TRPL, FE-SEM, HR-TEM, BET, and photocurrent. The photocatalytic water-splitting efficiency of MoO3@f-MWCNT and MoO3@g-C3N4 was measured under visible light (lambda >= 420 nm) irradiation using TEOA as a sacrificial reagent in DI water and natural seawater. The H-2 evolution rate in DI water for MoO3@f-MWCNT is 2313.56 mu mol g(-)(1) h(-)(1), and for MoO3@g-C3N4 is 2530.35 mu mol g(-1) h(-1) with an apparent quantum efficiency (AQE) of 6.38 and 6.93%, respectively. In natural seawater, the H-2 evolution rate is 2632.20 and 2845.06 mu mol g(-1) h(-1), with an AQE of 7.21 and 7.77%, respectively. The rate of H-2 evolution slightly increased in natural seawater than DI water. The Tafel slope values for MoO3@g-C3N4 and MoO3@f-MWCNT are 59 and 92 mV dec(-1), respectively. The lowest Tafel value of MoO3@g-C3N4 exhibited a faster rate of reaction. Thus, the surface interaction between the MoO3 and the porous g-C3N4 materials may create synergistic effects, which facilitate electron transport at the interface and significantly boost the photocatalytic activity. Thus, MoO3@g-C3N4 is a promising photocatalyst for renewable energy production.
Keywords: deionized water; electrochemicalHER; MoO3@f-MWCNT; MoO3@g-C3N4 nanocomposites; natural seawater; photocatalytic H-2 evolution